2011
DOI: 10.1007/s12663-011-0264-3
|View full text |Cite
|
Sign up to set email alerts
|

Metaanalysis of Maxillofacial Trauma in the Northern Districts of Kerala: One Year Prospective Study

Abstract: Purpose There is an increased incidence of maxillofacial trauma all over the world. A study was conducted to find out the epidemiological characteristics of maxillofacial trauma in Northern districts of Kerala. Methods All the trauma patients who attended the Department of Oral and Maxillofacial Surgery, Government Dental College, Calicut, Kerala during the period of 2006-2007 was included in the study. The incidence, prevalence, age and sex distribution, seasonal and daily variations and aetiology of maxillof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
44
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 21 publications
16
44
2
Order By: Relevance
“…Road traffic accidents remain the most frequent cause in the many developing countries, including India [8,9,[20][21][22][23][24]. The present study supports the findings of these earlier studies, showing that road traffic accidents represents 64 % of all etiological factors.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Road traffic accidents remain the most frequent cause in the many developing countries, including India [8,9,[20][21][22][23][24]. The present study supports the findings of these earlier studies, showing that road traffic accidents represents 64 % of all etiological factors.…”
Section: Discussionsupporting
confidence: 91%
“…This study revealed that the peak incidence of maxillofacial fractures occurred in the 21-30 year age group, with mean age of 29.6 years. Many surveys of maxillofacial fractures reported the same results concerning age [2,5,7,8,20]. The possible explanation for this was that younger persons involved in intense social interaction and higher rate of mobility, drive motor vehicles carelessly making them more susceptible to road transport accident and interpersonal assault.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Interpersonal and domestic violence, contact sports, alcohol and drug use, and falls are also strongly associated with facial injuries [9][10][11][12]. Furthermore, studies have demonstrated a strong association of facial injury with males, aged between 20-30 years and weekends [1,5,6,9,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The most common site of fracture in decreasing order were that of the zygomatic bone (88%) zygomatic arch (8.2%), and both the zygomatic bone and arch (3%). In a metaanalysis of maxillofacial trauma by Ravindran et al, 22 the most prevalent midface injury was in the zygomatic region (209, 36.4%), followed by orbital (102, 17.8%), Le Fort I (18, 3.1%), Le Fort II (43, 7.5%) and Le Fort III (10, 1.7%). Nasal bone fracture is the commonest isolated bone fractures.23 In our study, nasal bone fracture was present in 26 % of cases.…”
mentioning
confidence: 99%